HUBUNGAN PENGETAHUAN DENGAN TINGKATKECEMASAN PADA IBU PREMENOPAUSE USIA (40-50 TAHUN) - Rudi Karmi; Karwati; Murniati; Tampilang, Onnasis Kycken Yevrhaien (Program Studi Akuntansi IKOPIN, 2021)
Premenopause is a physiological condition on women have entered the agingprocess characterized by decreased levels of hormonal estrogen from the ovarieswhich play a very important role in reproduction and sexuality. When enteringpremenopause, women will experience anxiety, one of is in sexual intercourse. Thepurpose of this study was to determine the correlation between premenopause andthe level of anxiety on mothers during sexual intercourse in the Batujajar HealthCenter, West Bandung Regency. The method used in this study is a correlative analytic survey with a cross sectional design. The population in this study were 216women in the reproductive period until menopause at the Batujajar Health Center,West Bandung Regency, while the sample number were 68 respondents using theNon Probability Sampling technique by means of Accidental Sampling. The resultsof the study using the univariate test found that mothers who had good knowledgewere 4 respondents 6%, and those who experienced severe anxiety were 15respondents with a percentage of 15%. Meanwhile, the bivariate test using the chisquare test was found to have a correlation with the level of anxiety inpremenopausal mothers aged 40-50 with a value of p = 0.000 <ɑ = 0.05. Theconclusion of this study is there is a correlation between knowledge and anxietylevels in premenopausal mothers aged (40-50 years) at Batujajar health center. Thesuggestion of this study hopepully that the Public Health Center increasing theprovision of information or counseling periodically to mothers to increase theirknowledge and for further researchers to examine other factors.